Negative plate and lithium ion secondary battery
By designing a structure including the first graphite coating, a hybrid coating and a second graphite coating in the negative electrode sheet of the lithium-ion secondary battery, the silicon negative electrode is supported by polymer particles, and the interface deterioration caused by the expansion of the silicon negative electrode is solved. , achieving improvements in battery energy density and cycle stability.
Patent Information
- Application Number
- CN202510018901.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In lithium-ion secondary batteries, the expansion of the silicon negative electrode during circulation causes the interface between the negative electrode layer and the negative electrode current collector to deteriorate, and a higher proportion of binder is required to suppress expansion, which increases material cost and is difficult to increase the battery energy density and circulation. stability.
Design a negative electrode sheet, including a negative electrode current collector, a first graphite coating, a mixed coating and a second graphite coating, the mixed coating consists of silicon and polymer particles, the average particle size of the polymer particles is greater than the average particle of silicon The diameter is to avoid direct contact between silicon and the negative electrode current collector, and to suppress expansion of the silicon negative electrode.
It effectively suppresses the expansion of the silicon negative electrode, reduces material costs, improves battery energy density and cycle stability, and reduces the total amount of negative electrode adhesive.
Smart Images

Figure CN119419217A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode sheet and a lithium ion secondary battery using the negative electrode sheet. Background Art
[0002] As a secondary battery, lithium-ion batteries have outstanding advantages such as high energy density, high output power density, long cycle life, extremely low self-discharge rate, wide temperature adaptability range, and short charging time. Lithium-ion batteries have not only successfully replaced lead-acid batteries in the field of power batteries, but also play an important role in the fields of national defense, military, and aerospace, and are gradually replacing nickel-hydrogen and lead-acid batteries to achieve iterative upgrades of equipment.
[0003] At the same time, people have put forward higher requirements on the performance of lithium-ion batteries, requiring lithium-ion batteries to have higher energy density. Therefore, it is necessary to use high-gram capacity positive electrode materials or negative electrode materials to improve battery energy density.
[0004] The theoretical capacity of graphite anode is only 372mAh / g, which has basically reached its limit and it is difficult to make further breakthroughs. To further improve the energy density of batteries, it is necessary to redesign from the perspective of materials. The capacity of silicon-based anode is higher, and its theoretical capacity can reach 4200mAh / g. At present, silicon anode is usually mixed with graphite to improve energy density.
[0005] However, this solution requires a higher proportion of binder for the negative electrode, and the interface between the negative electrode layer and the negative electrode current collector deteriorates due to the expansion of the silicon negative electrode during the cycle. The main reason is that when silicon is in direct contact with the current collector, due to its excessive expansion, it slowly peels off the negative electrode current collector during the cycle, resulting in rapid cycle decay. At the same time, in order to suppress the expansion of the silicon negative electrode, a higher proportion of binder is required, which will increase the material cost. Summary of the invention
[0006] In order to avoid the deterioration of the interface between the negative electrode layer and the negative electrode current collector caused by the cyclic expansion of the silicon negative electrode, the purpose of the present invention is to provide a negative electrode sheet and a lithium-ion secondary battery, which can suppress the expansion of the silicon negative electrode while reducing the material cost, and improve the battery energy density while improving the cycle stability.
[0007] The present invention achieves the technical effects through the following technical solutions: In a first aspect, one of the objectives of the present invention is to provide a negative electrode sheet, comprising a negative electrode current collector and a first graphite coating, a mixed coating, and a second graphite coating sequentially arranged from the inside to the outside in a direction away from the negative electrode current collector, the first graphite coating being arranged on the surface of the negative electrode current collector, the first graphite coating comprising a first graphite, the second graphite coating comprising a second graphite, the mixed coating comprising silicon and polymer particles, and the average particle size D1 of the polymer particles being greater than the average particle size D2 of the silicon.
[0008] Preferably, the mixed coating further comprises a third graphite, and the average particle size D1 of the polymer particles is greater than the average particle size D3 of the third graphite. The third graphite is artificial graphite or natural graphite.
[0009] Preferably, in the mixed coating, the average particle size D1 of the polymer particles is 5-15 μm, the average particle size D2 of the silicon is 3-10 μm, and the average particle size D3 of the third graphite is 3-10 μm.
[0010] Preferably, in the mixed coating, the polymer particles account for 5% to 20% of the total weight of the mixed coating, and the polymer particles are polymer particles with bonding ability, preferably one or more of polyvinylidene fluoride PVDF, polymethyl methacrylate PMMA, and styrene-butadiene rubber SBR.
[0011] Preferably, the thickness of the mixed coating is 10% to 30% of the total thickness of the coating in the negative electrode sheet, and the sum of the thickness of the first graphite coating and the second graphite coating is 70% to 90% of the total thickness of the coating in the negative electrode sheet. In this way, the amount of binder used in the first graphite coating and the second graphite coating is the same as that of the conventional graphite coating, and the mixed coating accounts for a small proportion in the negative electrode sheet. Even if a higher proportion of binder is used, the total amount of binder used in the negative electrode can be greatly reduced, thereby reducing material costs.
[0012] Preferably, the thickness of the first graphite coating is 40-60 μm, the thickness of the mixed coating is 15-30 μm, and the thickness of the second graphite coating is 30-50 μm.
[0013] Preferably, the average particle size of the first graphite in the first graphite coating and the second graphite in the second graphite coating is 5 to 20 μm. The average particle sizes of the first graphite and the second graphite may be equal or unequal. For example, the average particle sizes of the first graphite and the second graphite are both 15 μm, or the average particle size of the first graphite is 5 μm and the average particle size of the second graphite is 10 μm.
[0014] The first graphite in the first graphite coating is artificial graphite or natural graphite; natural graphite is preferred, which can improve the adhesion between the coating and the foil and reduce the cost.
[0015] The second graphite in the second graphite coating is artificial graphite or natural graphite; artificial graphite is preferred to ensure the high-rate charging performance of the battery cell.
[0016] Preferably, the compacted density of the first graphite coating is 1.4~1.7 g / cc, and the porosity is 22%~36%; the compacted density of the second graphite coating is 1.4~1.7 g / cc, and the porosity is 22%~36%; the compacted density of the mixed coating is 1.1~1.5 g / cc, and its porosity is 32%~50%.
[0017] Preferably, the first graphite coating, the mixed coating and the second graphite coating also contain a conductive agent and a binder, wherein the conductive agent is independently selected from at least one of conductive carbon black SP and carbon nanotubes CNT; the binder is independently selected from at least two of carboxymethyl cellulose CMC, polyacrylic acid PAA and styrene-butadiene rubber SBR.
[0018] Preferably, in the first graphite coating, the weight ratio of the first graphite, the conductive agent, and the binder is (95~97): (0.5~2): (2~3); in the second graphite coating, the weight ratio of the second graphite, the conductive agent, and the binder is (95~97): (0.5~2): (2~3). The component ratios of the first graphite coating and the second graphite coating may be the same or different. For example, in the first graphite coating, the weight ratio of the first graphite, the conductive agent, and the binder is 95:2:3, and in the second graphite coating 4, the weight ratio of the second graphite, the conductive agent, and the binder is 97:0.5:2.5; or, in the first graphite coating and the second graphite coating, the weight ratio of the first graphite or the second graphite, the conductive agent, and the binder is 95:2:3.
[0019] Preferably, in the mixed coating, the ratio of silicon to the third graphite can fluctuate from 1:9 to 9:1, as long as the weight ratio of the silicon to the third graphite, the conductive agent, the binder, and the polymer particles is (75-91.5): (1-2): (3.5-5): (5-20). In this way, the content of the polymer particles is 5%-20% of the weight of the mixed coating, and the battery performance is optimal.
[0020] In a second aspect, the present invention further provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet as described above.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. A mixture of pure silicon and polymer particles is used between the first graphite coating and the second graphite coating, which can avoid direct contact between silicon and the negative electrode current collector, effectively inhibit the expansion and rebound of the silicon negative electrode, and improve the cycle stability while increasing the battery energy density.
[0022] 2. The polymer particles in the mixed coating play a supporting role in the middle layer, which not only reduces the compaction density of the middle layer, but also provides more expansion space for the silicon negative electrode and allows more electrolyte to penetrate into the middle layer, thereby improving the battery cycle performance and rate performance.
[0023] 3. The first graphite coating and the second graphite coating are pure graphite coatings, and the unit dosage of the binder is the same as that of the conventional graphite coating. The mixed coating accounts for a small proportion in the negative electrode. Even if a higher proportion of binder is used, the total binder dosage of the negative electrode can be greatly reduced, thereby reducing the material cost while suppressing the expansion of the silicon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the negative electrode sheet of the present invention.
[0025] In the figure: 1-negative electrode current collector, 2-first graphite coating, 3-mixed coating, 3.1-polymer particles, 4-second graphite coating. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In this specification, similar reference numerals represent similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0027] In the description of the present invention, the term "average particle size" refers to the volume average particle size D of the particles. V 50.
[0028] On the one hand, the negative electrode sheet provided by the present invention is Figure 1 As shown, it includes a negative electrode current collector 1 and a first graphite coating 2, a mixed coating 3 and a second graphite coating 4 arranged in sequence from the inside to the outside in a direction away from the negative electrode current collector 1, the first graphite coating 2 is arranged on the surface of the negative electrode current collector 1, the first graphite coating 2 includes a first graphite, the second graphite coating 4 includes a second graphite, the mixed coating 3 includes silicon and polymer particles 3.1, and the average particle size D1 of the polymer particles 3.1 is greater than the average particle size D2 of the silicon.
[0029] In some embodiments, the mixed coating 3 further comprises a third graphite, and the average particle size D1 of the polymer particles 3.1 is greater than the average particle size D3 of the third graphite. The third graphite is artificial graphite or natural graphite.
[0030] In some embodiments, in the mixed coating 3, the average particle size D1 of the polymer particles 3.1 is 5~15μm, specifically, it can be 5μm, 7μm, 8μm, 9μm, 10μm, 12μm, 13μm, 15μm, etc.; the average particle size D2 of the silicon is 3~10μm, specifically, it can be 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, etc.; the average particle size D3 of the third graphite is 3~10μm, specifically, it can be 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, etc. In this way, it can not only ensure that the average particle size D1 of the polymer particles 3.1 in the mixed coating 3 is larger than the average particle size D2 of silicon and the average particle size D3 of the third graphite in the mixed coating 3, but also ensure that the polymer particles 3.1 contained in the mixed coating 3 can protrude from the mixed coating 3, so that the mixed coating 3 can play a supporting role as an intermediate layer, which can not only reduce the compaction density of the intermediate layer, but also provide more expansion space for the silicon negative electrode and allow more electrolyte to penetrate into the intermediate layer, thereby improving the battery cycle performance.
[0031] In some embodiments, in the mixed coating 3, the polymer particles 3.1 account for 5% to 20% of the total weight of the mixed coating, and the polymer particles are polymer particles with bonding ability, preferably one or more of polyvinylidene fluoride PVDF, polymethyl methacrylate PMMA, and styrene-butadiene rubber SBR. The above polymer particles can be obtained commercially, for example, by purchasing the emulsion of the above materials and selecting the polymer particle emulsion with the required average particle size.
[0032] In some embodiments, the thickness of the mixed coating 3 is 10% to 30% of the total thickness of the negative electrode sheet, and the sum of the thickness of the first graphite coating 2 and the second graphite coating 4 is 70% to 90% of the total thickness of the negative electrode sheet. In this way, the amount of binder used in the first graphite coating and the second graphite coating is the same as that of the conventional graphite coating, and the mixed coating accounts for a small proportion in the negative electrode sheet. Even if a higher proportion of binder is used, the total amount of binder used in the negative electrode can be greatly reduced, thereby reducing material costs.
[0033] The thickness of the first graphite coating 2 is 40-60 μm, specifically, 40 μm, 43 μm, 47 μm, 50 μm, 52 μm, 56 μm, 60 μm, etc. The thickness of the mixed coating 3 is 15-30 μm, specifically, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, etc. The thickness of the second graphite coating 4 is 30-50 μm. Specifically, it can be 30 μm, 34 μm, 37 μm, 40 μm, 42 μm, 46 μm, 50 μm, etc.
[0034] In some embodiments, the average particle size of the first graphite in the first graphite coating 2 and the second graphite in the second graphite coating 4 is 5 to 20 μm, specifically, 5 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm, etc. The average particle size of the first graphite and the second graphite may be equal or unequal. For example, the average particle size of the first graphite and the second graphite is both 15 μm, or the average particle size of the first graphite is 5 μm and the average particle size of the second graphite is 10 μm.
[0035] The first graphite in the first graphite coating 2 is artificial graphite or natural graphite; natural graphite is preferred, which can improve the adhesion between the coating and the foil and reduce the cost.
[0036] The second graphite in the second graphite coating 4 is artificial graphite or natural graphite; artificial graphite is preferred to ensure the high-rate charging performance of the battery cell.
[0037] In some embodiments, the compaction density of the first graphite coating 2 is 1.4~1.7 g / cc, and the porosity is 22%~36%; the compaction density of the second graphite coating 4 is 1.4~1.7 g / cc, and the porosity is 22%~36%; the compaction density of the mixed coating is 1.1~1.5 g / cc, and its porosity is 32%~50%.
[0038] In some embodiments, the first graphite coating 2, the mixed coating 3, and the second graphite coating 4 also contain a conductive agent and a binder, wherein the conductive agent is independently selected from at least one of conductive carbon black SP and carbon nanotubes CNT; and the binder is independently selected from at least two of carboxymethyl cellulose CMC, polyacrylic acid PAA, and styrene-butadiene rubber SBR. The conductive agent is preferably conductive carbon black SP, the binder of the first graphite layer and the second graphite layer is preferably CMC+SBR (weight ratio 1:1), and the binder of the mixed coating is preferably CMC+PAA+SBR (weight ratio 2:5:3), which can reduce material costs.
[0039] In some embodiments, in the first graphite coating, the weight ratio of the first graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-3); in the second graphite coating, the weight ratio of the second graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-3). Specifically, the weight ratio can be (95:2:3), (95.5:1.5:3), (96:2:2), (96.5:1:2.5), (97:0.5:2.5), etc. The component ratios of the first graphite coating and the second graphite coating can be the same or different. For example, in the first graphite coating, the weight ratio of the first graphite, the conductive agent, and the binder is 95:2:3, and in the second graphite coating 4, the weight ratio of the second graphite, the conductive agent, and the binder is 97:0.5:2.5; or, in the first graphite coating and the second graphite coating, the weight ratio of the first graphite or the second graphite, the conductive agent, and the binder is 95:2:3.
[0040] In some embodiments, in the mixed coating 3, the ratio of silicon to the third graphite can fluctuate from 1:9 to 9:1, as long as the weight ratio of the silicon to the third graphite, the conductive agent, the binder, and the polymer particles is (75-91.5): (1-2): (3.5-5): (5-20). Specifically, the weight ratio can be (75:2:3:20), (80:2:2:16), (85:2:3:10), (88:1.5:3.5:7), (90:2:2:6), (91.5:1:2.5:5), etc.
[0041] In a second aspect, the present invention provides a lithium-ion secondary battery, comprising the negative electrode sheet as described above.
[0042] The present invention is further described below by way of examples. The reagents, materials and instruments used in the following descriptions are conventional reagents, conventional materials and conventional instruments unless otherwise specified, and are all commercially available. The reagents and materials involved can also be prepared by known methods. For example, conductive carbon black SP comes from TIMCAL, Switzerland, styrene-butadiene rubber SBR comes from SBR AWG101 of Haodian Technology Co., Ltd., and methyl cellulose CMC comes from Weiyi CMC2300. The methods in the embodiments, unless otherwise specified, are conventional methods in the art.
[0043] Embodiment 1: (1) Preparation method of negative electrode sheet: The slurry of the first graphite coating: the weight ratio of the first graphite, the conductive agent, and the binder is 96:1:3 (this ratio is the dry material weight ratio), wherein the first graphite is natural graphite with an average particle size of 15 μm, the conductive agent is conductive carbon black SP, and the binder is a mixture of SBR and CMC in a weight ratio of 1:1.
[0044] Slurry preparation: first dissolve CMC in water, add SP for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, then add graphite for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, and finally add SBR for slow dispersion, the dispersion line speed is 3m / s, and the dispersion time is 0.5h.
[0045] The slurry of the mixed coating: the weight ratio of silicon + third graphite, conductive agent, binder and polymer particles is 83.5:1.5:5:10 (this ratio is the dry material weight ratio); wherein, the weight ratio of silicon to third graphite is 50:33.5, the third graphite is artificial graphite with an average particle size D3 of 5 μm, the average particle size D2 of silicon is 5 μm, the conductive agent is conductive carbon black SP, the binder is a mixture of CMC, PAA and SBR in a weight ratio of 2:5:3, and the polymer particles are polyvinylidene fluoride PVDF with an average particle size D1 of 7 μm.
[0046] Slurry preparation: first dissolve CMC and PAA in water, then add SP for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, then add graphite + silicon for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, and finally add SBR for slow dispersion, the dispersion line speed is 3m / s, and the dispersion time is 0.5h.
[0047] The slurry of the second graphite coating: the weight ratio of the second graphite, the conductive agent and the binder is 96:1:3 (this ratio is the dry material weight ratio); wherein the second graphite is artificial graphite with an average particle size of 15 μm, the conductive agent is conductive carbon black SP, and the binder is a mixture of SBR and CMC in a weight ratio of 1:1.
[0048] Slurry preparation: first dissolve CMC in water, add SP for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, then add graphite for dispersion, the dispersion line speed is 12m / s, and the dispersion time is 2h, and finally add SBR for slow dispersion, the dispersion line speed is 3m / s, and the dispersion time is 0.5h.
[0049] Coating: The three layers of slurry are applied on the copper foil surface in layers synchronously by extrusion coating; The thickness of the first graphite coating layer is 60 μm, the thickness of the mixed coating layer is 20 μm, and the thickness of the second graphite coating layer is 40 μm.
[0050] After rolling and drying, the compacted density of the first graphite coating is 1.6 g / cc and its porosity is 27%; the compacted density of the second graphite coating is 1.7 g / cc and its porosity is 26%; the compacted density of the mixed coating is 1.4 g / cc and its porosity is 36.4%.
[0051] (2) Preparation of lithium-ion secondary batteries: The positive electrode sheet, separator and electrolyte of the lithium ion battery prepared according to the conventional method in the art and the negative electrode sheet prepared by the present invention are assembled into a 2Ah soft-pack battery according to the general process for preparing lithium ion batteries.
[0052] Example 2 The difference between the negative electrode sheet and the preparation method thereof and the lithium-ion battery provided in this embodiment and those in Embodiment 1 is that in the slurry of the mixed coating, the average particle size D1 of the polymer particles is 15 μm.
[0053] Other conditions are the same as those in Example 1.
[0054] The compacted density of the first graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 26%; the compacted density of the mixed coating is 1.37 g / cc, and its porosity is 37.7%.
[0055] Example 3 The difference between the negative electrode sheet, preparation method thereof and lithium-ion battery provided in this embodiment and embodiment 1 is that in the slurry of the first graphite coating, the first graphite is natural graphite with an average particle size of 10 μm; in the slurry of the mixed coating, the average particle size D1 of the polymer particles is 15 μm.
[0056] The compacted density of the first graphite coating is 1.56 g / cc, and its porosity is 29.1%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 28.7%; the compacted density of the mixed coating is 1.37 g / cc, and its porosity is 37.7%.
[0057] Other conditions are the same as those in Example 1.
[0058] Example 4 The difference between the negative electrode sheet, preparation method thereof and lithium-ion battery provided in this embodiment and embodiment 1 is that in the slurry of the mixed coating, the average particle size D1 of the polymer particles is 15 μm, the average particle size D2 of silicon is 3 μm, and the average particle size D3 of the third graphite is 3 μm.
[0059] The compacted density of the first graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the second graphite coating is 1.7 g / cc, and its porosity is 25%; the compacted density of the mixed coating is 1.45 g / cc, and its porosity is 34.1%.
[0060] Other conditions are the same as those in Example 1.
[0061] Example 5 The difference between the negative electrode sheet, preparation method thereof and lithium-ion battery provided in this embodiment and embodiment 1 is that: in the slurry of the mixed coating, the average particle size D1 of the polymer particles is 15 μm, the average particle size D2 of silicon is 3 μm, and the average particle size D3 of the third graphite is 6 μm; in the slurry of the second graphite coating, the second graphite is artificial graphite with an average particle size of 10 μm.
[0062] The compacted density of the first graphite coating is 1.58 g / cc, and its porosity is 28.2%; the compacted density of the second graphite coating is 1.52 g / cc, and its porosity is 28%; the compacted density of the mixed coating is 1.38 g / cc, and its porosity is 37.2%.
[0063] Other conditions are the same as those in Example 1.
[0064] Example 6 The difference between the negative electrode sheet, preparation method thereof and lithium ion battery provided in this embodiment and those in Embodiment 1 is that in the slurry of the second graphite coating, the weight ratio of the second graphite, the conductive agent and the binder is 95.5:1.5:3.
[0065] The compacted density of the first graphite coating is 1.57 g / cc, and its porosity is 28.6%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 27.9%; the compacted density of the mixed coating is 1.4 g / cc, and its porosity is 36.4%.
[0066] Other conditions are the same as those in Example 1.
[0067] Example 7 The difference between the negative electrode sheet, preparation method thereof and lithium ion battery provided in this embodiment and embodiment 1 is that: in the slurry of the first graphite coating, the weight ratio of the first graphite, the conductive agent and the binder is 96.5:1:2.5; in the slurry of the mixed coating, the weight ratio of silicon + the third graphite, the conductive agent, the binder and the polymer particles is 75:2:3:20, and the weight ratio of silicon to the third graphite is 9:1; in the slurry of the second graphite coating, the weight ratio of the second graphite, the conductive agent and the binder is 95.5:1.5:3.
[0068] The compacted density of the first graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the mixed coating is 1.35 g / cc, and its porosity is 38.6%.
[0069] Other conditions are the same as those in Example 1.
[0070] Example 8 The difference between the negative electrode sheet, preparation method thereof and lithium ion battery provided in this embodiment and embodiment 1 is that: in the slurry of the first graphite coating, the weight ratio of the first graphite, the conductive agent and the binder is 96.5:1:2.5, in the slurry of the mixed coating, the weight ratio of silicon + the third graphite, the conductive agent, the binder and the polymer particles is 75:2:3:20, and the weight ratio of silicon to the third graphite is 1:5; in the slurry of the second graphite coating, the weight ratio of the second graphite, the conductive agent and the binder is 95.5:1.5:3.
[0071] The compacted density of the first graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the mixed coating is 1.35 g / cc, and its porosity is 38.6%.
[0072] Other conditions are the same as those in Example 1.
[0073] Example 9 The difference between the negative electrode sheet, preparation method thereof and lithium-ion battery provided in this embodiment and embodiment 1 is that in the slurry of the mixed coating, the weight ratio of silicon + third graphite, conductive agent, binder and polymer particles is 75:2:3:20, and the weight ratio of silicon to third graphite is 5:2.
[0074] The compacted density of the first graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the second graphite coating is 1.6 g / cc, and its porosity is 27%; the compacted density of the mixed coating is 1.33 g / cc, and its porosity is 39.5%.
[0075] Other conditions are the same as those in Example 1.
[0076] Example 10 The difference between the negative electrode sheet, preparation method thereof and lithium-ion battery provided in this embodiment and those in Embodiment 1 is that in the slurry of the mixed coating, the weight ratio of silicon, conductive agent, binder and polymer particles is 83.5:1.5:5:10, and no third graphite is contained.
[0077] The compacted density of the first graphite coating and the second graphite coating is 1.6 g / cc, and the porosity is 27%; the compacted density of the second graphite coating is 1.6 g / cc, and the porosity is 26%; the compacted density of the mixed coating is 1.3 g / cc, and the porosity is 40.9%.
[0078] Other conditions are the same as those in Example 1.
[0079] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the coating of the negative electrode sheet has only one layer, the slurry does not contain polymer particles, and 88 parts of natural graphite with a particle size of 15 μm, 8 parts of silicon, 1 part of conductive agent, and 3 parts of binder are mixed and dispersed uniformly to form a slurry.
[0080] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the coating of the negative electrode sheet does not contain the first graphite coating, but only has two layers, namely the mixed coating and the second graphite coating, and the mixed coating is arranged on the surface of the negative electrode current collector, and the mixed coating comprises a silicon-based active material and a pressure-elastic additive, and the pressure-elastic additive is three-dimensional graphene.
[0081] Comparative Example 3: The difference between Comparative Example 3 and Example 10 is that the coating of the negative electrode sheet has three layers, and the mixed coating contains silicon and graphite but does not contain polymer particles.
[0082] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that, in the mixed coating, the average particle size D1 of the polymer particles is 6 μm, the average particle size D2 of the silicon is 8 μm, and the average particle size D3 of the third graphite is 9 μm.
[0083] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that, in the mixed coating, the average particle size D1 of the polymer particles is 6 μm, the average particle size D2 of the silicon is 6 μm, and the average particle size D3 of the third graphite is 6 μm.
[0084] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that the average particle size D1 of the polymer particles in the mixed coating is 8 μm, the average particle size D2 of silicon is 10 μm, and the average particle size D3 of the third graphite is 6 μm.
[0085] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that the average particle size D1 of the polymer particles in the mixed coating is 9 μm, the average particle size D2 of silicon is 8 μm, and the average particle size D3 of the third graphite is 10 μm.
[0086] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that the average particle size D1 of the polymer particles in the mixed coating is 8 μm, the average particle size D2 of silicon is 8 μm, and the average particle size D3 of the third graphite is 9 μm.
[0087] Comparative Example 9: The difference between Comparative Example 9 and Example 1 is that the average particle size D1 of the polymer particles in the mixed coating is 8 μm, the average particle size D2 of silicon is 9 μm, and the average particle size D3 of the third graphite is 8 μm.
[0088] Comparative Example 10 The difference between Comparative Example 10 and Example 10 is that the average particle size D1 of the polymer particles in the mixed coating is 6 μm, and the average particle size D2 of silicon is 9 μm.
[0089] Performance Test: The negative electrode sheets and 2Ah soft-pack batteries obtained in the above examples and comparative examples were subjected to performance tests, and the performance test results are shown in Table 1. The test method is as follows: [Capacity retention rate after 1000 cycles at room temperature] At 25°C, charge to 4.50V at a constant current of 1C, charge to 4.50V at a constant voltage of 0.05C, and then discharge to 3.0V at a discharge rate of 1C. Repeat this charge and discharge cycle 1000 times, and measure the discharge capacity at the first cycle and the discharge capacity at the 1000th cycle. Calculate the capacity retention rate Q after 1000 cycles according to the following formula: Capacity retention rate Q = Q1000 / Q1*100%.
[0090] [Battery liquid retention]: Battery liquid retention = liquid injection volume - (original weight of package - battery weight after secondary sealing - airbag weight), unit is g.
[0091] [Negative electrode full charge rebound rate]: Negative electrode full charge rebound rate = (negative electrode thickness in fully charged state - thickness of negative electrode after rolling) / (negative electrode thickness after rolling - copper foil thickness) * 100%.
[0092] Table 1 Performance test results of the electrodes and batteries corresponding to the embodiments and comparative examples
[0093] It can be seen from the performance test results in Table 1 that in the coating of the negative electrode sheet, when polymer particles are added or the average particle sizes of polymer particles, silicon and graphite are selected to be outside the range disclosed in the present invention, the expansion rate of the silicon negative electrode increases and the performance of the battery decreases to varying degrees.
[0094] Specifically, it can be seen from the test results of Examples 1-9 and Comparative Example 1 that if the negative electrode sheet has only one coating layer and the slurry does not contain polymer particles, silicon is in direct contact with the negative electrode current collector, and the battery performance is significantly reduced due to its excessive expansion rate.
[0095] It can be seen from the test results of Examples 1-9 and Comparative Example 2 that when the coating of the negative electrode sheet does not contain the second graphite coating, but only has the mixed coating and the second graphite coating, and the mixed coating is disposed on the surface of the negative electrode current collector, the mixed coating is easily peeled off the surface of the current collector after rebounding, resulting in deterioration of the cycle performance.
[0096] It can be seen from the test results of Example 10 and Comparative Example 3 that when the negative electrode sheet has three layers of coating but the mixed coating does not contain polymer particles, it cannot ensure that more electrolyte penetrates into the electrode sheet, which is not conducive to cycle performance.
[0097] It can be seen from the test results of Examples 1-9 and Comparative Examples 4 to 9 that if the polymer particles in the mixed coating slurry are smaller than the particle size of silicon and graphite, the polymer particles cannot play a supporting role therein, which is not conducive to the penetration of electrolyte and has little buffering effect on the rebound of the negative electrode, resulting in a significant decrease in battery performance.
[0098] It can be seen from the test results of Example 10 and Comparative Example 10 that the average particle size D1 of the polymer particles in the mixed coating is smaller than the average particle size D2 of silicon, the expansion rate of the silicon negative electrode increases and the performance of the battery decreases to varying degrees.
[0099] Therefore, the negative electrode sheet provided by the present invention and the battery prepared with the negative electrode sheet can effectively inhibit the expansion of the silicon negative electrode and improve the battery cycle performance.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a first graphite coating, a mixed coating and a second graphite coating arranged in sequence from the inside to the outside in a direction away from the negative electrode current collector, wherein the first graphite coating comprises a first graphite, and the second graphite coating comprises a second graphite, characterized in that: The mixed coating includes silicon and polymer particles, and the average particle size D1 of the polymer particles is greater than the average particle size D2 of the silicon.
2. The negative electrode sheet according to claim 1, characterized in that: The mixed coating further comprises a third graphite, and the average particle size D1 of the polymer particles is greater than the average particle size D3 of the third graphite.
3. The negative electrode sheet according to claim 2, characterized in that: In the mixed coating, the average particle size D1 of the polymer particles is 5-15 μm, the average particle size D2 of the silicon is 3-10 μm, and the average particle size D3 of the third graphite is 3-10 μm.
4. The negative electrode sheet according to claim 2, characterized in that: In the mixed coating, the polymer particles account for 5% to 20% of the total weight of the mixed coating, and the polymer particles are polymer particles with bonding ability.
5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the mixed coating is 10% to 30% of the total thickness of the coating in the negative electrode sheet, and the sum of the thickness of the first graphite coating and the second graphite coating is 70% to 90% of the total thickness of the coating in the negative electrode sheet.
6. The negative electrode sheet according to claim 1, characterized in that: The average particle size of the first graphite in the first graphite coating layer and the second graphite in the second graphite coating layer is 5 to 20 μm.
7. The negative electrode sheet according to claim 1, characterized in that: The compaction density of the first graphite coating is 1.4~1.7g / cc, and the porosity is 22%~36%; the compaction density of the second graphite coating is 1.4~1.7g / cc, and the porosity is 22%~36%; the compaction density of the mixed coating is 1.1~1.5g / cc, and its porosity is 32%~50%.
8. The negative electrode sheet according to claim 2, characterized in that: The first graphite coating, the mixed coating and the second graphite coating also contain a conductive agent and a binder, wherein the conductive agent is independently selected from at least one of conductive carbon black and carbon nanotubes; and the binder is independently selected from at least two of carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber.
9. The negative electrode sheet according to claim 8, characterized in that: In the first graphite coating, the weight ratio of the first graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-3); In the second graphite coating, the weight ratio of the second graphite, the conductive agent, and the binder is (95-97): (0.5-2): (2-3); In the mixed coating, the weight ratio of the silicon and the third graphite, the conductive agent, the binder, and the polymer particles is (75-91.5): (1-2): (3.5-5): (5-20).
10. A lithium ion secondary battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 9.
Citation Information
Patent Citations
Negative pole piece, preparation method thereof and lithium ion battery
CN116914148A
Silicon-carbon negative pole piece, preparation method thereof and lithium ion battery
CN116936741A
Sandwich type silicon negative electrode plate, preparation method thereof and lithium ion battery
CN117525287A
Cited By
Electrode plate containing silicon negative electrode, battery and preparation method of electrode plate
CN120600764A